Expressive Study on The Novel "Dear Oppa" By Nurima Thama - Nabila Fathihatun Dahlya; Nas Haryati Setyaningsih (Jurnal Syntax Transformation, 2023)
This study aims to get results to describe the expressive approach to the novel entitled Dear Oppa by Nurima Thama. The purpose of this study is to describe the expression of the author who expresses his ideas in the work he has created. The method used in this study is qualitative descriptive. Data analysis techniques used in this study are data reduction, data presentation and conclusions. This research data collection technique is by reading carefully, marking data findings in dialogue or narrative, reading other references that have a relationship with the topic of research discussion and presenting research findings. The results of this study are in the form of an analysis of expression studies which are divided into two parts, namely the personality of the main character and the description of the author's expression in the novel.